Maternal recall of a history of early-onset preeclampsia, late-onset preeclampsia, or gestational hypertension: a validation study - Anouk Bokslag; Anne B. Fons; Laurien J. Zeverijn; Pim W. Teunissen; Christianne J.M. de Groot (Taylor & Francis Group, 2020)
Objective: This study assessed women's ability to recall different types of hypertensive disorders of pregnancy because of its disproportionate cardiovascular risk later in life. Methods: Participants were 5-10 years post-partum with a history of early-onset-, late-onset preeclampsia, or gestational hypertension. Recall was assessed by questionnaire and compared to medical records. Results: Questionnaire-based recall of early-onset preeclampsia had high sensitivity and specificity, late-onset preeclampsia poor sensitivity and high specificity and gestational hypertension had very poor sensitivity and high specificity. Conclusion: Early-onset preeclampsia can accurately be assessed using a simple questionnaire. Recall of late-onset preeclampsia and gestational hypertension was not accurate.